2020
DOI: 10.1186/s13741-020-00143-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional performance and 30-day postoperative mortality after emergency laparotomy—a retrospective, multicenter, observational cohort study of 1084 patients

Abstract: Background: Despite the importance of predicting adverse postoperative outcomes, functional performance status as a proxy for frailty has not been systematically evaluated in emergency abdominal surgery. Our aim was to evaluate if the Eastern Cooperative Oncology Group (ECOG) performance score was independently associated with mortality following high-risk emergency abdominal surgery, in a multicentre, retrospective, observational study of a consecutive cohort. Methods: All patients aged 18 or above undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 55 publications
(62 reference statements)
0
27
0
Order By: Relevance
“…Some studies suggested that the number of walking steps was related to performance status [ 31 ]. As performance status is also one of the important factors for surgical indication and outcome [ 32 ], the pattern of the decrease and recovery in walking steps after NACRT is likely to be an indicator for the continuation of follow-up surgery or a predictor for postoperative mortality in patients with esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that the number of walking steps was related to performance status [ 31 ]. As performance status is also one of the important factors for surgical indication and outcome [ 32 ], the pattern of the decrease and recovery in walking steps after NACRT is likely to be an indicator for the continuation of follow-up surgery or a predictor for postoperative mortality in patients with esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Octogenarians versus patients aged 70 to 79. Analysis of 19,407 patients from 4 studies 11,15,19,28 showed that the risk of 30-day mortality was significantly higher in octogenarians compared with patients aged 70 to 79 (OR: 1.21, 95% CI 1.13e1.31; P < .00001) (Fig 4, C). The between-study heterogeneity was low (I 2 ¼ 0%, P ¼ .65), and the certainty of the evidence was judged to be high (Supplementary Table 2).…”
Section: Comparisonsmentioning
confidence: 93%
“…The following parameters were analyzed: age, gender, body mass index (BMI), ASA-PS, pre-operative Charlson score 6 , the pre-operative fall risk assessment 7 , mFI-5 8 , ECOG-PS 9 , type of anesthesia, indication(s) for surgery, surgery site, duration of anesthesia, duration of surgery, volume of fluid administered during surgery, volume of blood loss, the presence of intra-operative transfusion (red cell concentrates [RCCs], fresh frozen plasma [FFP], platelets, and albumin), the use of an electroencephalogram (EEG) monitor, the duration of hospital stay, post-operative complications (hypoxia, delirium diagnosed by psychiatrists, and aspiration pneumonia), and 30-day survival after surgery. Hypoxia was defined as 'oxygen saturation (SpO2) under 95% with room air after surgery', and aspiration pneumonia defined as 'a newly diagnosed pneumonia after surgery with an episode of vomiting or aspiration'.…”
Section: Methodsmentioning
confidence: 99%
“…It is also known that worse frailty as evaluated by the ECOG-PS and mFI-5 and other assessment tools is associated with the surgical outcome in adult patients [9][10][11] . Especially among older patients, pre-and/or post-operative frailty or comorbidity are wellrecognized as predictive factors of mortality, in addition to the functional evaluation scales 12,13 .…”
Section: Relationship Between Requirement Of General Anesthesia and Mortality In Emergency Casesmentioning
confidence: 99%
See 1 more Smart Citation